Direct Synthesis of Intermetallic Platinum-Alloy Nanoparticles Highly Loaded on Carbon Supports for Efficient Electrocatalysis - Yoo, Tae Yong; Yoo, Ji Mun; Sinha, Arun Kumar; Bootharaju, Megalamane S.; Jung, Euiyeon; Lee, Hyeon Seok; Lee, Byoung-Hoon; Kim, Jiheon; Antink, Wytse Hooch; Kim, Yong Min; Lee, Jongmin; Lee, Eungjun; et al. (AMER CHEMICAL SOC, 2020)
Compared to nanostructured platinum (Pt) catalysts, ordered Pt-based intermetallic nanoparticles supported on a carbon substrate exhibit much enhanced catalytic performance, especially in fuel cell electrocatalysis. However, direct synthesis of homogeneous intermetallic alloy nanocatalysts on carbonaceous supports with high loading is still challenging. Herein, we report a novel synthetic strategy to directly produce highly dispersed MPt alloy nanoparticles (M = Fe, Co, or Ni) on various carbon supports with high catalyst loading. Importantly, a unique bimetallic compound, composed of [M(bpy)(3)](2+) (bpy = 2,2'-bipyridine) and [PtCl6](2-) anion, evenly decomposes graphene oxide on carbon surface and forms uniformly sized intermetallic nanoparticles with a nitrogen-doped carbon protection layer. The excellent oxygen reduction reaction (ORR) activity and stability of the representative reduced graphene oxide (rGO)-supported L1(0)-FePt catalyst (37 wt %-FePt/rGO), exhibiting 18.8 times higher specific activity than commercial Pt/C catalyst without degradation over 20 000 cycles, well demonstrate the effectiveness of our synthetic approach toward uniformly alloyed nanoparticles with high homogeneity.
Keywords: OXYGEN REDUCTION REACTION; FEPT NANOPARTICLES; BIMETALLIC CATALYSTS; MESOPOROUS CARBON; L1(0)-FEPT; CHEMISTRY; REMOVAL; GREEN; CO